1999
DOI: 10.1016/s0009-9236(99)70138-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rifampin and rifabutin on the pharmacokinetics and pharmacodynamics of a combination oral contraceptive

Abstract: In this study, rifampin (600 mg daily) was a more significant inducer of ethinyl estradiol and norethindrone clearance than rifabutin (300 mg daily), but neither agent reversed the suppression of ovulation caused by oral contraceptives. The carefully monitored oral contraceptive administration and the limited exposure to rifamycins may restrict the application of this study to clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
4
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 31 publications
2
89
4
2
Order By: Relevance
“…The cytochrome P450 (CYP) enzyme system in the liver plays a significant role in drug metabolism, and drugs (possibly including the herbal medication, St John's Wort) that induce these enzymes can cause increased elimination of contraceptive steroids, resulting in reduced reliability and, consequently, unplanned pregnancy. 3 A variety of potent enzyme inducers known to have deleterious effects on hormonal contraceptives include some antiepileptics (carbamazepine, oxcarbazepine, phenytoin, phenobarbital, primidone, topiramate), [16][17][18][19] antibiotics (rifampicin, rifabutin), [20][21][22][23][24] antifungals (griseofulvin), 25 protease inhibitors (amprenavir, atazanavir, nelfinavir, lopinavir, saquinavir, ritonavir), 26 and non-nucleoside reverse transcriptase inhibitors (efavirenz, nevirapine). 27 There have been sporadic reports of Implanon failure due to suspected interaction with concomitantly administered drugs, resulting in intrauterine 10,11,28 or ectopic [29][30][31] pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…The cytochrome P450 (CYP) enzyme system in the liver plays a significant role in drug metabolism, and drugs (possibly including the herbal medication, St John's Wort) that induce these enzymes can cause increased elimination of contraceptive steroids, resulting in reduced reliability and, consequently, unplanned pregnancy. 3 A variety of potent enzyme inducers known to have deleterious effects on hormonal contraceptives include some antiepileptics (carbamazepine, oxcarbazepine, phenytoin, phenobarbital, primidone, topiramate), [16][17][18][19] antibiotics (rifampicin, rifabutin), [20][21][22][23][24] antifungals (griseofulvin), 25 protease inhibitors (amprenavir, atazanavir, nelfinavir, lopinavir, saquinavir, ritonavir), 26 and non-nucleoside reverse transcriptase inhibitors (efavirenz, nevirapine). 27 There have been sporadic reports of Implanon failure due to suspected interaction with concomitantly administered drugs, resulting in intrauterine 10,11,28 or ectopic [29][30][31] pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Among women taking rifampin and OCs, 75% experienced intermenstrual bleeding, and 6% became pregnant (Reimers and Jezek, 1971). The effects of rifampin on the disposition kinetics of ethinylestradiol resulting in a substantial decrease in area under the curve have been thoroughly studied (Barditch-Crovo et al, 1999). Likewise, van Dijke and Weber (1984) reported an array of case studies involving women taking concomitant griseofulvin and OCs who reported menstrual cycle disturbances and pregnancies.…”
Section: Downloaded Frommentioning
confidence: 99%
“…18,19) Clinically relevant plasma concentrations of EE 2 are very low (Ͻ2 nM). 7) These values indicate that the possibility of substrate inhibition of EE 2 3-sulfation in human liver can be completely ruled out. K m values for the 2-hydroxylation and 3-glucuronidation of EE 2 in pooled liver microsomes were 3.34 and 23.3 mM, respectively, and the K m value for the 3-sulfation of EE 2 in pooled liver cytosol was 2.85 mM ( Table 1).…”
Section: Discussionmentioning
confidence: 93%
“…Plasma concentrations of EE 2 achieved during normal therapy are very low (Ͻ2 nM). 7) However, most previous in vitro studies used substantially high EE 2 substrate concentrations (Ͼ10 mM). A recent study using human hepatocytes in vitro at a substrate concentration of 1 nM demonstrated that the major EE 2 metabolites are direct conjugates, with hydroxylation representing minor pathways, and suggested that the production of EE 2 -3-sulfate was increased by pretreatment of hepatocytes with rifampicin.…”
mentioning
confidence: 99%